Pengaruh Jenis Air Perawatan terhadap Kuat Tekan Beton pada Usia 28 Hari - Miftakhul Fahri; Felly Misdalena; Vanita Kesumawati Yacub (Institut Teknologi Garut, 2025)
Concrete quality is highly influenced by the curing process, including the type of water used, as it affects cement hydration. This study compares the effects of using seawater and freshwater on the compressive strength of concrete, with eight cylindrical specimens (four cured with seawater and four with freshwater) tested at 28 days in accordance with SNI standards. The results show that concrete cured in seawater achieved an average compressive strength of 18.88 MPa, which is higher than that of concrete cured in freshwater (14.94 MPa). This increase is presumed to be due to the presence of Ca2+, Mg2+, and SO42- ions in seawater, which accelerate cement hydration, although the Cl- content remains a concern due to its potential to cause reinforcement corrosion. This study contributes to the utilization of seawater as an alternative curing medium in coastal regions where freshwater is scarce, while emphasizing the need for further research to assess the long-term effects on structural durability.